The Association Between Suicide Attempts, Anxiety, and Childhood Maltreatment Among Adolescents and Young Adults With First Depressive Episodes - Chen, Hui; Li, Wen; Cao, Xia; Liu, Peiqu; Liu, Jiali; Chen, Xianliang; Luo, Chenyuli; Liang, Xiaoxi; Guo, Huijuan; Zhong, Shaoling; Wang, Xiaoping; Zhou, Jiansong (Frontiers in Psychiatry, 2021)
Objective: Adolescents and young adults are susceptible to high-risk behaviours such as self-harm and suicide. However, the impact of childhood maltreatment on suicide attempts in adolescents and young adults with first episode of depression remains unclear. This study examined the association between suicide attempts and childhood maltreatment among adolescents and young adults with first depressive episodes. Methods: A total of 181 adolescents and young adults with first depressive episodes were included. The Child Trauma Questionnaire (CTQ), Beck Anxiety Inventory (BAI), and Patient Health Questionnaire-2 (PHQ-2) were used to assess childhood maltreatment and the severity of anxiety and depressive symptoms respectively. The suicide item in the MINI-International Neuropsychiatric Interview (M.I.N.I.) 5.0 was used to assess the suicide attempts. Logistic regression analyses were used to explore the associated factors of suicide attempts. Results: The prevalence of SA in the total sample was 31.5% (95% CI=24.9%-38.1%). Multivariate logistic regression analyses revealed that the diagnosis of bipolar disorder (OR=2.18, 95% CI=1.07-4.40), smoking (OR=2.64, 95% CI=1.10-6.37), anxiety symptoms (OR=1.05, 95% CI=1.02-1.08), and childhood maltreatment (OR=1.04, 95% CI=1.01-1.07) were potential associated factors of SA. In addition, anxiety symptoms had a mediating effect on the relationship between childhood maltreatment and SA. Conclusion: Adolescents and young adults with first depressive episodes and having experiences of childhood maltreatment are at a high risk of suicide. The severity of anxiety symptoms may mediate the relation between childhood maltreatment and suicide attempts in this group of patients.